2010
DOI: 10.1111/j.1559-3584.2010.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Design Implications of Fuel Cell Power for Sealift Ships

Abstract: Fuel cell technologies provide clean and efficient power solutions for both stationary and mobile applications. For shipboard applications, most studies published so far have focused on ship service power or on propulsion power for small vessels with moderate power requirements. Using a military sealift vessel as the platform, this project aims at investigating the implications of implementing fuel cells as the primary power source on a large military cargo ship. A notional solid oxide fuel cell (SOFC) module … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Cherednichenko and Serbin (2018) and Cherednichenko et al (2019) analysed the capabilities of thermo-chemical technologies for the conversion of different hydrocarbons on ships. As reported by Sun et al (2010), the SOFC-GT system for the Large Medium Speed Roll-on/Rolloff sealift ship has significant potential in reducing nitrogen oxides emission and fuel consumption. Four SOFC modules and one gas turbine generator with a special catalytic combustor were proposed to construct a hybrid SOFC-GT engine with 24 MW of total electrical power.…”
Section: Intoductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Cherednichenko and Serbin (2018) and Cherednichenko et al (2019) analysed the capabilities of thermo-chemical technologies for the conversion of different hydrocarbons on ships. As reported by Sun et al (2010), the SOFC-GT system for the Large Medium Speed Roll-on/Rolloff sealift ship has significant potential in reducing nitrogen oxides emission and fuel consumption. Four SOFC modules and one gas turbine generator with a special catalytic combustor were proposed to construct a hybrid SOFC-GT engine with 24 MW of total electrical power.…”
Section: Intoductionmentioning
confidence: 91%
“…The main efforts in the field of marine engineering are currently aimed at increasing the energy efficiency of the production, transmission, and use of energy, which is possible only if innovations are based on fundamental science achievements, together with the creation and implementation of new, more reliable and durable materials, equipment and technologies. Fuel cells are one of the promising directions for solving problems of providing electric energy to consumers in various complex conditions (Sun et al 2010;Díaz-de-Baldasano et al 2014;Han et al 2015;Chen et al 2017Chen et al , 2018.…”
Section: Intoductionmentioning
confidence: 99%
“…One can even envision different kinds of power plants, for example, fuel cells and gas turbines, on the same ship (Sun, Stebe, & Kennell, 2010). Integrating all the power sources and loads to form an efficient and reliable power network becomes the overarching task for electrified vehicle PMS/EMS.…”
Section: Control Implications Of Electrified Powertrainmentioning
confidence: 99%
“…It was also pointed out that diesel fuel reforming was the key to efficient operation of fuel cells in hybrid systems [8] . Sun [9] et al compared a diesel-fueled SOFC-GT hybrid system, a diesel engine, and a gas turbine using a military marine vessel as a platform. Studies had shown that the SOFC-GT hybrid system could save 20-50% of fuel and basically had no NOx emissions.…”
Section: Introductionmentioning
confidence: 99%